2011
DOI: 10.1111/j.1753-0407.2011.00115.x
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive risk assessments of diabetic patients from seven Asian countries: The Joint Asia Diabetes Evaluation (JADE) program*

Abstract: It is possible to use a web-based protocol to establish a registry for risk stratification and facilitate early intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 22 publications
7
43
3
Order By: Relevance
“…In brief, all the enrolled participants would undergo an intake assessment, which was a comprehensive risk assessment including measurement of risk factors for cardiovascular and renal complications and eye and foot assessment. The case manager, an advanced practice nurse, would review the examinations results, assess the cardiovascular risks, and stratify participants into risk groups ("very high," "high," "medium," and "low") according to the modified Joint Asia Diabetes Evaluation cardiovascular risk stratification flowchart (20). The participants were then assigned to receive appropriate interventions and education provided by a team of multidisciplinary health care professionals, including Associate Consultants in family medicine (AC intervention), registered nurses, advanced practice nurses (nurse intervention), and allied health professionals, according to stratified risk level and HbA 1c level.…”
Section: Ramp-dm Interventionmentioning
confidence: 99%
“…In brief, all the enrolled participants would undergo an intake assessment, which was a comprehensive risk assessment including measurement of risk factors for cardiovascular and renal complications and eye and foot assessment. The case manager, an advanced practice nurse, would review the examinations results, assess the cardiovascular risks, and stratify participants into risk groups ("very high," "high," "medium," and "low") according to the modified Joint Asia Diabetes Evaluation cardiovascular risk stratification flowchart (20). The participants were then assigned to receive appropriate interventions and education provided by a team of multidisciplinary health care professionals, including Associate Consultants in family medicine (AC intervention), registered nurses, advanced practice nurses (nurse intervention), and allied health professionals, according to stratified risk level and HbA 1c level.…”
Section: Ramp-dm Interventionmentioning
confidence: 99%
“…The design, implementation and adoption of the JADE Program have been published. [10][11][12] In brief, the JADE Program is a web-based programme that uses information technology to facilitate healthcare professionals to create a diabetes registry and to deliver evidence-based care tailored to patients' risk profiles. All enrolled patients gave written informed consent to undergo comprehensive assessment, which includes clinical and demographic information and laboratory investigations at enrolment and at regular intervals thereafter.…”
Section: Study Subjects and Settingmentioning
confidence: 99%
“…19 From our analysis of nationwide data, the highest prevalence was in females aged 40e65 years (46.15%), but this prevalence was lower than that reported in the JADE program or in the study by Xu and colleagues in China. 18,19 In our analysis, the prevalence of dyslipidemia in patients with microvascular complications remained stable. In patients with macrovascular complications, including all CVD and CVA, the prevalence of associated dyslipidemia decreased in both genders from 2000 to 2009.…”
Section: Discussionmentioning
confidence: 81%
“…17 Data from the Joint Asia Diabetes Evaluation (JADE) program from eight areas in Asia including Taiwan also showed that dyslipidemia and hypertension affected 76.8% and 84.6% of the patients, respectively. 18 In a study conducted by Xu et al in Beijing, China, the prevalence of lipid disorder was as high as 63.8% in the Chinese population in the Beijing area. 19 From our analysis of nationwide data, the highest prevalence was in females aged 40e65 years (46.15%), but this prevalence was lower than that reported in the JADE program or in the study by Xu and colleagues in China.…”
Section: Discussionmentioning
confidence: 98%